2021
DOI: 10.1016/j.cub.2020.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Ventro-dorsal Hippocampal Pathway Gates Novelty-Induced Contextual Memory Formation

Abstract: Summary Novelty facilitates memory formation and is detected by both the dorsal and ventral hippocampus. Although dentate granule cells (GCs) in the dorsal hippocampus are known to mediate the formation of novelty-induced contextual memories, the required pathways and mechanisms remain unclear. Here we demonstrate that a powerful excitatory pathway from mossy cells (MCs) in the ventral hippocampus to dorsal GCs is necessary and sufficient for driving dorsal GC activation in novel environment explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 75 publications
8
54
1
Order By: Relevance
“…As sections progressed to more caudal and ventral regions, the number of GFP+ hilar cells increased significantly (Figure 3b5–b10). A very small number of weakly‐labeled GFP+ cells were observed in the CA3c region of some sections (Figure 3b7–b9), consistent with previous reports (Fredes et al, 2020; Yeh et al, 2018). Importantly, the GFP+ axon was largely restricted to the IML of the DG throughout the entire septotemporal axis of the DG.…”
Section: Resultssupporting
confidence: 91%
“…As sections progressed to more caudal and ventral regions, the number of GFP+ hilar cells increased significantly (Figure 3b5–b10). A very small number of weakly‐labeled GFP+ cells were observed in the CA3c region of some sections (Figure 3b7–b9), consistent with previous reports (Fredes et al, 2020; Yeh et al, 2018). Importantly, the GFP+ axon was largely restricted to the IML of the DG throughout the entire septotemporal axis of the DG.…”
Section: Resultssupporting
confidence: 91%
“…It thus may not be sufficient to extrapolate findings from dMCs to all MCs across the HPC longitudinal axis. Of note, an elegant recent study using in vivo microscopy showed increased vMC activity in novel versus familiar environments that was not due to locomotion differences (72), in line with our fiber photometry findings.…”
Section: Discussionsupporting
confidence: 90%
“…Less attention has been devoted to the role of MCs, especially vMCs, in behavior relevant to neuropsychiatric disease including learning, memory, novelty, and anxiety, however there is growing research interest in these topics. Distinctions between vMCs and dMCs are supported by physiological (69-72), biochemical (27, 28), and anatomical (49, 72, 73) evidence. It thus may not be sufficient to extrapolate findings from dMCs to all MCs across the HPC longitudinal axis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Activity levels in granule cell populations have been shown to decrease over the time course of several minutes and more as the animal familiarizes itself with a novel environment 10,69,71 . However, how the population activity changes at the moment when the animal transitions into a novel environment is unclear.…”
Section: Discussionmentioning
confidence: 99%